Les dernières Amazones : réflexions sur la contestation de l’ordre politique masculin pendant la Fronde - Sophie Vergnes (Les Cahiers de Framespa)
During the Middle Ages and early modern times, the royal absolutism theoreticians made power an exclusively male field because of an alleged female inferiority. But this changing didn’t please aristocracy, favourable to a temperate monarchy. All the more so as women had always been active rulers among them. The Fronde was to some extent a way to express this discontent. The civil troubles gave noble women a way to challenge the patriarchal aspect of monarchy. But the failure of the Fronde was also the one of these female fighters, as women and as aristocrats. Nevertheless, the battle against patriarchal order didn’t end under the personal rule of Louis XIV. Writing was among the means that allowed these women to go on claiming power in the public sphere.